'You don't have to sleep with a man to get how to survive': Girl's perceptions of an intervention study aimed at improving sexual and reproductive health and schooling outcomes - Linda Mason; Garazi Zulaika; Anna Maria van Eijk; Eunice Fwaya; David Obor; Penelope Phillips-Howard; Elizabeth Nyothach (Public Library of Science (PLoS), 2022)
In sub-Saharan Africa, girls suffer from high rates of morbidity and mortality, enduring high exposure to sexual and reproductive health harms. Staying in school helps protect girls from such harms. Focus group discussions were conducted in a rural, impoverished area of Kenya with adolescent girls participating in a 4-arm cluster randomised controlled trial, evaluating menstrual cups, cash transfer, or combined cups plus cash transfer against controls. To explore girls' perceptions of how trial interventions affected their SRH risks and schooling, semi-structured discussions were held at baseline, midline, and study end. Data was explored using thematic analysis. At baseline there were no discernible differences between the 4 intervention groups regarding their perceptions of relationships with boys/men, and difficulties attending or remaining in school. Midline and endline discussions found that narratives from those receiving cash transfer only, or alongside a cup were similar; girls noted fewer pregnancies and less school dropout, attributed to the cash transfer reducing the need for transactional sex. Lower absenteeism was reported by the cup only group, with perceived minimal effect on pregnancy and dropout. Girls in control and cup only groups described feeling valued through inclusion, benefitting from puberty and hygiene education. Although seemingly having little effect on reducing pregnancy or dropout, these inputs reportedly empowered girls, whilst cash transfer girls were emboldened to refuse male sexual advances. Girls noticed benefits from trial interventions, with a reduction in transactional sex and resulting pregnancy impacting on school dropout, or reduced menstrual related absenteeism. Education and study inclusion were perceived as important. Future programmes should consider alleviating material deprivation which prevents girls from attending or performing at school through schemes such as cash transfer, alongside hygiene and education packages. This will empower girls to refuse unwanted sex and understand risks, in addition to motivating academic achievement and school completion. Trial registration: ClinicalTrials.gov NCT03051789.